Phylogeography and genetic diversity of Ulmus elongata (Ulmaceae), a Tertiary relict tree with extremely small populations (PSESP) - Yakun Wang; Xiankun Wang; Junyuan Wu; Jun Yang; Yanpei Liu; Peng Guo; Fude Shang; Nan Lin (BMC Plant Biology)
Abstract Background Assessing the current status and identifying the mechanisms threatening endangered plants are significant challenges and fundamental to biodiversity conservation, particularly for protecting Tertiary relict trees and plant species with extremely small populations (PSESP). Ulmus elongata (Ulmus, Ulmaceae) with high values for the ornamental application, is a Tertiary relict tree species and one of the members from PSESP in China. Currently, the wild populations of U. elongata have been threatened by excessive deforestation and urbanization, but limited knowledges of its genetic diversity seriously hinder conservation efforts. Therefore, a further study on the genetic diversity and drivers of genetic pattern in U. elongata is crucial for preserving genetic resources and can serve as a reference for other Tertiary relict plants and PSESP under climate change. Results Here, a total of 12 populations from 70 individuals of U. elongata were collected covering its geographical distribution in China. Utilizing chloroplast genome datasets, we found that U. elongata exhibited remarkably low nucleotide diversity and gene flow (π = 0.00013, Nm = 0.03). Analysis of molecular variance (AMOVA) showed that genetic variation in U. elongata occurs mainly between eight clades (60.95%). The Mantel tests indicated a significant correlation between genetic differentiation and geographical distances (r = 0.3777, p < 0.05) in U. elongata populations. A notable phylogeographic structure was identified in U. elongata, comprising eight distinct haplogroups (N ST = 0.917, G ST = 0.876, p < 0.05), which was attributed to the global cooling in the East Asia and Quaternary climate oscillations. Conclusions Overall, our study using Ulmus elongata as a representative supported the hypothesis that plants belonging to Tertiary relict species and PSESP simultaneously exhibits significantly lower genetic diversity compared to those are either Tertiary relict species or PSESP individually. Furthermore, the low genetic diversity and significant genetic differentiation in U. elongata populations can be primarily ascribed to a combination of factors, including habitat fragmentation resulting from human activities, populations contraction during LGM and small population sizes. This provides a crucial foundation for guiding conservation efforts and implementing management strategies for other Tertiary relict tree species and PSESP. Our findings also provide evidence for the important roles of East Asian monsoon system and climate oscillations in shaping the phylogeographic pattern in subtropical broad-leaved forests.